Comparison of ergonomic risk assessment outputs from OWAS and REBA in forestry timber harvesting - Enez, Korhan; Nalbantoğlu, Sibel Seçil (Elsevier BV, 2019)
Abstract Globally, work-related (musculoskeletal disorders (MSDs) are one of the most important health problems encountered by ergonomists. Forest work, especially logging harvesting, is traditionally recognized as one of the most difficult types of physical work and has distinct characteristics. Harvesting works in forestry are composed of the following work stages: logging, skidding, and loading. This study aimed to examine risk factors of MSDs associated with different work postures during harvesting under variable external conditions by comparing work stages using the Ovako Working posture Assessment System (OWAS) and Rapid Entire Body Assessment (REBA). A statistically significant difference was observed between the two methods. While the difference in risk to the musculoskeletal system was statistically significant in different work stages using REBA, logging and skidding were assigned to the same risk level using OWAS. Easy-to-use ergonomic hand tools should be developed that are suitable for working conditions and help reduce MSD risk in forestry workers.
Keywords: 15. Life on land